PEMBINAAN WARGA JEMAAT MELALUI LAYANAN KHOTBAH MIMBAR MENGENAI MELURUSKAN JALAN HIDUP DALAM LUKAS 3: 7-20 SEBAGAI UPAYA UNTUK MEMAHAMI DAN MEMAKNAI MASA ADVEN - Agnes Magdelina Kolly; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2025)
Advent is a period of preparation for the coming of the Lord. The Imanuel Surbung GMIT in Alor Regency celebrates Advent for four consecutive weeks. Usually, during this time of waiting, many Christians everywhere are busy preparing for the coming of the Lord in the moment of Christmas celebration by outwardly preparing their needs. Therefore, through the pulpit sermon service, the author teaches in the form of ‘preaching’ by giving lectures and asking the congregation questions, with the aim of enabling the congregation to understand, reflect on and interpret the meaning of the word delivery. Questions are also asked so that the teaching through sermons is not one-way, so that the congregation also thinks, reflects and reflects. The aim is to invite the congregation to truly interpret and understand the advent season and through teaching in the form of sermons to provide a correct understanding of the appropriate way to welcome and await the coming of Jesus Christ through the word of God in the reading of the text Luke 3: 7-20 and the theme of straightening the path of life. As a result, the sermon delivered consisted of several reflective questions and two Christian values that became implications for the congregation, namely living in repentance and living in humility and becoming a blessing as an effort to straighten out one's path in life while awaiting the coming of the Lord.